An investigation into the effects of aspalathin on myocardial glucose transport using cardiomyocytes from control and obesity-induced insulin resistant rats, and terminally differentiated H9C2 cells - Smit, Sybrand Engelbrecht (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: Introduction: Rooibos is an indigenous South African plant ingested as herbal tea and well-known for its strong anti-oxidant effects. Rooibos has shown to have cardioprotective properties in vitro and in vivo, but the role of individual Rooibos flavonoids in cardioprotection still remains unclear. This in vitro study investigated Aspalathin, a dihydrochalcone unique to rooibos, for (i) cardioprotective effects in the context of age- and obesity-induced insulin resistance, known to attenuate myocardial glucose uptake and utilization and (ii) the applicable signaling pathways involved. Methods: Male Wistar rats were allocated into three groups: 16-30 weeks feeding with either standard rat chow (C) or a high-fat, high-caloric diet (HFD), or 6-7 weeks feeding with C. Cardiomyocytes were isolated by collagenase perfusion digestion, using a Langendorff apparatus and glucose uptake determined by 2-[3H]-deoxyglucose (2DG) accumulation using liquid scinitillation analysis. In addition, H9C2 cells were differentiated into cardiomyocyte analogs and also used. Viability was tested by either Trypan-blue exclusion, JC-1-staining or PI-staining and FACS analysis, and metabolic activity determined with an ATP assay. Intracellular signaling was evaluated using Western blot analysis and commercially available antibodies to PKB and AMPK. Results: HFD caused significant increases in body weight gain, visceral adiposity, fasting and non-fasting blood glucose, serum insulin levels and an elevated HOMA-IR index. HFD cardiomyocytes were glucose uptake resistant to increasing concentration of insulin (1-100nM). Aspalathin (10uM) and insulin (10nM) co-incubation for 45mins induced 2DG uptake in younger control cardiomyocytes, while incubation for longer than 90 mins with aspalathin (10uM) induced 2DG uptake independent of insulin in younger control cardiomyocytes and differentiated H9C2 cells. Aspalathin improved metabolic activity and membrane integrity in cultured, differentiated H9C2 cells. Aspalathin also enhanced insulin-mediated 2DG uptake in older control cells, but failed to induce 2DG uptake in HFD cells. Acute treatment with aspalathin (15min) in conjunction with insulin in vitro significantly increased PKB activation and AMPK expression. Extended treatment with aspalathin (90mins) in young cells resulted in significantly increased AMPK activation/expression ratio, whereas aspalathin co-treatment with insulin resulted in increased PKB activation. Aged rats had significantly higher AMPK expression and activation compared to young rats. Conclusions: A high-fat, high-sucrose diet of at least 16 weeks is an effective model to induce insulin-resistant, obese rats. Aspalathin and insulin co-treatment for 45 mins in cardiomyocytes isolated from young rats, and co-treatment for 90 mins in aged, control rats, induced glucose uptake. Aspalathin of at least 90 mins induced glucose uptake in cardiomyocytes from young Wistar rats, and differentiated H9C2 cells. In addition, it resensitized the insulin-signaling pathway in cardiomyocytes, possibly through activation of PKB and AMPK, resulting in an additive response. These beneficial effects of aspalathin may ultimately be due to its antioxidant capacity, receptor-mediated actions or role in GLUT4 translocation, but this remains to be established.